DNA Probe and Nucleic Acid Hybridization for Plant Virus Detection - Pissawan Chiemsombat; Wichai Kositratana; Supat Attathom; Thira Sutabutra; Nuchnard Sae-aung (Agriculture and Natural Resources, 1990)
The DNA Probe for detection of tomato yellow leaf curl virus (TYLCV) was constructed by using the oligolabelling method. Cloned TYLCV - DNA Component A in a Bluescript vector was linearized by cutiing at EcoRI site, denatured and primed with random hexanucleotide primer. The complementary DNA strand, labeled with 32P, was completely synthesized by Klenow polymerase filling - in reaction. The cDNA probe was denatured and used in virus detection by nucleic acid hybridization technique. The probe obtained had sensitive at 1 picagram level of template DNA, and reacted well with viral DNA either in crude extract or in DNA preparation of infected tomato tissues. The probe can also detect viral DNA from squash blotted samples of infected tissues and viruliferous whitefly vector